The Historical Evolution of Public Administration Toward Smart Governance: Examining Its Impact on Citizen Engagement and Administrative Efficiency - Akhmad Riduan; Yosaphat Danis Murtiharso; Tomi Apra Santosa; Mulyadi Mulyadi; Umar Sako (Citra Media Publishing, 2026)
The historical evolution of public administration reflects a fundamental transformation from traditional bureaucratic structures toward increasingly participatory, digital, and technology-driven governance systems. This transition, encompassing traditional public administration, New Public Management, e-government, digital governance, and contemporary smart governance, has reshaped the relationship between government institutions, administrative processes, and citizens. Despite the growing implementation of smart governance, empirical evidence regarding its simultaneous contribution to citizen engagement and administrative efficiency remains fragmented, particularly when positioned within the historical transformation of public administration. This study aims to examine the evolution of public administration toward smart governance and quantitatively assess the impact of smart governance implementation on citizen engagement and administrative efficiency. A quantitative explanatory research design was employed using a cross-sectional survey involving citizens who had experience accessing digital public services. Data were collected through a structured questionnaire measuring smart governance implementation, citizen engagement, and administrative efficiency and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that smart governance implementation has a positive and significant effect on citizen engagement by strengthening access to information, digital participation, government–citizen interaction, responsiveness, and opportunities for involvement in public decision-making. Smart governance also significantly improves administrative efficiency through streamlined procedures, faster service delivery, enhanced information integration, reduced administrative complexity, and more effective utilization of public resources.